2012
DOI: 10.1016/j.jcrs.2012.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metal and flexible sub-Tenon cannulas

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Different types of cannulas are currently used for STB, but ST cannula is considered the gold standard. [1314] Hence, the efficacy of all other cannulas is compared to the ST cannula. Mather compared a simple 20-gauge intravenous cannula to ST and has found it equally effective.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of cannulas are currently used for STB, but ST cannula is considered the gold standard. [1314] Hence, the efficacy of all other cannulas is compared to the ST cannula. Mather compared a simple 20-gauge intravenous cannula to ST and has found it equally effective.…”
Section: Discussionmentioning
confidence: 99%
“…Onset of akinesia was shorter in alkalanised preparation of lidnocaine [36] . Akinesia was less with a metal subtenon canula compared to flexible medium or flexible posterior cannulas [37] . In a hospital-based randomized comparative interventional study of uncomplicated cataract surgery who received either peribulbar block or posterior sub-tenon block, Igana et al [38] reported that both routes of administering anesthetic substances is comparable in providing adequate akinesia and analgesia for cataract surgery with minimal complications, and both techniques are effective and safe.…”
Section: Akinesiamentioning
confidence: 85%
“…It is assumed in the reported cases in the literature, that rigid metal posterior cannulas were used. Riad et al 5 compared flexible cannulas with rigid ones for STA with comparable akinesia results and presumably better safety. A low-volume sub-Tenons such as 1.5 mL has been indicated to have ‘good anaesthesia’ and ‘varying akinesia’ but no comparable data with the conventional larger volumes 6…”
Section: Descriptionmentioning
confidence: 99%